Critical preparedness and operational response actions directed for the acute and post-acute COVID-19 pandemic in Brazil: the experience of a nationwide outpatient healthcare group. Issue 15 (16th April 2021) - Torres, Ulysses S.; Kerbauy, Daniella M.B.; Barrancos, Janaína T.G.; D'Ippolito, Giuseppe; Lázari, Carolina S.; Granato, Celso Francisco H.; Rizzatti, Edgar Gil; Meirelles, Gustavo S.P.
Abstract : Abstract: While the new Coronavirus Disease 2019 (COVID-19) pandemic rapidly spread across the world, South America was reached later in relation to Asia, Europe and the United States of America (USA). Brazil concentrates now the largest number of cases in the continent and, as the disease speedily progressed throughout the country, prompt and challenging operational strategies had to be taken by institutions caring for COVID-19 and non-COVID-19 patients in order to assure optimal workflows, triage, and management. Although hospitals in the USA, Europe and Asia have shared their experience on this subject, little has been discussed about such strategies in South America or by the perspective of outpatient centers, which are paramount in the radiology field. This article shares the guidelines adopted early in the pandemic by a nationwide outpatient healthcare center composed by a network of more than 200 patient service centers and nearly 2, 000 radiologists in Brazil, discussing operational and patient management strategies, staff protection, changes adopted in the fellowship program, and the effectiveness of such measures.